2020
DOI: 10.3390/cells9102328
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Remodeling of Altered Autophagy-Lysosomal Pathway by a Phosphopeptide in Lupus

Abstract: The phosphopeptide P140/Lupuzor, which improves the course of lupus disease in mice and patients, targets chaperone-mediated autophagy (CMA), a selective form of autophagy that is abnormally upregulated in lupus-prone MRL/lpr mice. Administered intravenously to diseased mice, P140 reduces the expression level of two major protein players of CMA, LAMP2A and HSPA8, and inhibits CMA in vitro in a cell line that stably expresses a CMA reporter. Here, we aimed to demonstrate that P140 also affects CMA in vivo and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…While some of the therapeutic effects of rapamycin and metformin may derive from targeting B cell autophagy, this process is affected more clearly by rigerimod ( 111 ). Rigerimod disrupts chaperone–mediated autophagy, likely affecting the MHC–II–restricted presentation of endogenous antigens to autoreactive T cells ( 112 , 137 ). In mice, rigerimod suppresses autoimmune responses without compromising anti–viral immunity ( 138 , 139 ).…”
Section: B Cell Metabolism and Autophagy As Therapeutic Targetsmentioning
confidence: 99%
“…While some of the therapeutic effects of rapamycin and metformin may derive from targeting B cell autophagy, this process is affected more clearly by rigerimod ( 111 ). Rigerimod disrupts chaperone–mediated autophagy, likely affecting the MHC–II–restricted presentation of endogenous antigens to autoreactive T cells ( 112 , 137 ). In mice, rigerimod suppresses autoimmune responses without compromising anti–viral immunity ( 138 , 139 ).…”
Section: B Cell Metabolism and Autophagy As Therapeutic Targetsmentioning
confidence: 99%
“…In this direction, the immunosuppressive properties exerted by MSCs can be proven useful to halt the B cell proliferation and differentiation (Table 3). Previous studies have demonstrated that SLE patients are characterized by autophagy-activated CD4+ T helper and CD8+ cytotoxic T cells [118,119]. Specifically, CD4+ and CD8+ T cell subsets are characterized by defective mitochondria, mitochondrial hyperpolarization, ATP depletion and increased apoptosis [118,119].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Previous studies have demonstrated that SLE patients are characterized by autophagy-activated CD4+ T helper and CD8+ cytotoxic T cells [118,119]. Specifically, CD4+ and CD8+ T cell subsets are characterized by defective mitochondria, mitochondrial hyperpolarization, ATP depletion and increased apoptosis [118,119]. MSCs can effectively rescue the T cells from apoptosis using tunneling nanotubes to transfer their mitochondria.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…This promiscuous peptide sequence was identified using ex vivo peptide screening techniques (143). This epitope is recognized by IgG antibodies and CD4+ T cells from H-2 k MRL/lpr and H-2 d/z (NZB × NZW)F1 lupus-prone mice (143,144). With i.v.…”
Section: Lupuzormentioning
confidence: 99%
“…A 70K-U1RNP 131-151 T helper epitope was identified in NZBxNZW F1 and MRL/ Fas(lpr) mice, which led to further identification of SmD1 and hnRNP A2/B1 epitopes in each strain. Of interest the SmD 95-119 epitope recognized by anti-Sm antibodies is homologous to an Epstein-Barr virus EBNA I peptide, suggesting a mechanism for epitope spreading through bystander T helper cells (144,175). Certain nuclear antigens tend to induce epitope spreading to related other nuclear antigens in mouse models (Table 2).…”
Section: Autoantigens In Slementioning
confidence: 99%